Immunotherapy: a new standard of care in thoracic malignancies?: A summary of the European Respiratory Society research seminar of the Thoracic Oncology Assembly. Issue 2 (15th February 2018) - Costantini, Adrien; Grynovska, Marta; Lucibello, Francesca; Moisés, Jorge; Pagès, Franck; Tsao, Ming S.; Shepherd, Frances A.; Bouchaab, Hasna; Garassino, Marina; Aerts, Joachim G.J.V.; Mazières, Julien; Mondini, Michele; et al.
In May 2017, the second European Respiratory Society research seminar of the Thoracic Oncology Assembly entitled "Immunotherapy, a new standard of care in thoracic malignancies?" was held in Paris, France. This seminar provided an opportunity to review the basis of antitumour immunity and to explain how immune checkpoint inhibitors (ICIs) work. The main therapeutic trials that have resulted in marketing authorisations for use of ICIs in lung cancer were reported. A particular focus was on the toxicity of these new molecules in relation to their immune-related adverse events. The need for biological selection, currently based on immunohistochemistry testing to identify the tumour expression of programmed death ligand (PD-L)1, was stressed, as well as the need to harmonise PD-L1 testing and techniques. Finally, sessions were dedicated to the combination of ICIs and radiotherapy and the place of ICIs in nonsmall cell lung cancer with oncogenic addictions. Finally, an important presentation was dedicated to the future of antitumour vaccination and of all ongoing trials in thoracic oncology. An in-depth summary of the European Respiratory Society seminar on the use of immunotherapy in thoracic malignancies http://ow.ly/kKht30h6pkk